2001
DOI: 10.1063/1.1343473
|View full text |Cite
|
Sign up to set email alerts
|

Microwave surface resistance of YBa2Cu3Oy films covered by overdoped Y1−xCaxBa2Cu3Oy layers

Abstract: We have observed the reduction of the microwave surface resistance Rs of YBa2Cu3Oy films deposited on MgO substrates by covering the films with an overdoped Y1−xCaxBa2Cu3Oy layer. At low temperature, Rs of the YBa2Cu3Oy film covered by an Y1−xCaxBa2Cu3Oy (x=0.2) layer was half that of the single YBa2Cu3Oy film. On the other hand, the single Y1−xCaxBa2Cu3Oy (x=0.2) films did not exhibit low loss characteristics. The diffusion of Ca ions into the YBa2Cu3Oy layer was observed and the selective diffusion of Ca ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 12 publications
3
13
0
Order By: Relevance
“…Similarly, in other experiments peaks in the microwave losses have been observed at well-defined magnetic dc fields, which are attributed to individual Josephson vortices penetrating the grain-boundary junctions (Xin et al, 2000). Reduction of the surface resistance of YBa 2 Cu 3 O 7Ϫ␦ films at a given reduced temperature T/T c has been reported in studies in which the YBa 2 Cu 3 O 7Ϫ␦ films were covered with Y 1Ϫx Ca x Ba 2 Cu 3 O 7Ϫ␦ capping layers (Obara et al, 2001). This reduction has been attributed to a reduction of the grain-boundary losses due to Ca doping Obara et al, 2001); see Sec.…”
Section: G Microwave Propertiessupporting
confidence: 62%
See 3 more Smart Citations
“…Similarly, in other experiments peaks in the microwave losses have been observed at well-defined magnetic dc fields, which are attributed to individual Josephson vortices penetrating the grain-boundary junctions (Xin et al, 2000). Reduction of the surface resistance of YBa 2 Cu 3 O 7Ϫ␦ films at a given reduced temperature T/T c has been reported in studies in which the YBa 2 Cu 3 O 7Ϫ␦ films were covered with Y 1Ϫx Ca x Ba 2 Cu 3 O 7Ϫ␦ capping layers (Obara et al, 2001). This reduction has been attributed to a reduction of the grain-boundary losses due to Ca doping Obara et al, 2001); see Sec.…”
Section: G Microwave Propertiessupporting
confidence: 62%
“…With such heterostructures, for 24°grain boundaries in YBa 2 Cu 3 O 7Ϫ␦ films, critical current densities as high as 3.3ϫ10 5 A/cm 2 have been obtained at 77 K. These values equal the usual current densities measured for 7°boundaries at 77 K, or the typical current densities of 24°boundaries at 4.2 K (Hammerl et al, , 2001; for J c increases see also Berenov, Farvacque, et al, 2001). Obara et al (2001) reported that the surface resistance of YBa 2 Cu 3 O 7Ϫ␦ films is reduced by covering the films with Y 1Ϫx Ca x Ba 2 Cu 3 O 7Ϫ␦ capping layers. This reduction has been attributed to a reduction of the grainboundary losses due to Ca doping Obara et al, 2001); see Sec.…”
Section: Effects Of Dopingmentioning
confidence: 64%
See 2 more Smart Citations
“…1 GBs have attracted much interest for their basic physics as well as for their applications in superconductors, 2,3,4 and play a crucial role in microwave response and surface resistance R s of high-temperature superconducting films. 5,6,7,8,9,10,11,12,13 Electrodynamics of GB junctions can be described using the Josephson-junction model, and one of the most important parameters that characterize GB junctions is the critical current density J cj for Josephson tunneling current across GBs. 14,15,16 The J cj strongly depends on the misorientation angle of GBs.…”
Section: Introductionmentioning
confidence: 99%